Do registro ao documentário: uma tradução verbo-visual-sonora na Amazônia - Borges, Marlise (2009)
This research has proposed an analysis of the creation and the recreation process in the verb-sonorous work Tuyabaé Cuaá (The knowledge of the Ancient Pajés), whose author is the composer and writer Walter Freitas, born in Pará, Brazil a work which reverberates the Amazon culture and the author s fundamental knowledge of it. Its objective was to observe the process of cultural translation and the transformative mixes preset at the work, pointing the new ensemble which intercommunicates since ways, presuppositions and vehicles of a complex work of art. About notions of memory and métissage , the thoughts of authors like Jerusa Pires Ferreira and Amálio Pinheiro were utilized, moreover theoretical works such as Jesus Martin Barbero s and Serge Gruzinski s, that think the métissage and the relations between communication and culture in Latin America as a place of multi-confluence of diverse elements. The Semiotics of the Culture, beyond Iuri Lotman, Aron Gurévitch, and also using the party concept formulated by Mikhail Bakhtin, has grounded the followed courses, also providing a backup to its development. Tuyabaé Cuaá fulfils its function of recuperate and activate some kind of collective memory. Besides the intersemiotics translation, other recreation and translation processes were realized since Walter Freitas work. That s another phonographic register, Medievo Cabano . Therefore, it was presented, such as complementary experience of this paper, a sonorous re-lecture, funding the composer music with elements from medieval, baroque and renaissance period elements. It was also realized an experience in the visual creative field: the sense of sound has turn into image (eight paintings), established above the poetic and musical universe of Walter Freitas. To finalize, it was elaborated a proposition of a documentary work which, sharing new esthetics and diverse languages, could fit the kind of cinematographic production that, in the future, will be able to considerate the dimensions that point to ethnographic, overall to its deconstruction, and to the elements of the autobiography. Into this, everything also remits to subjective and reflexive discourses about the world